Positive Thinking among Sixth Grade Learners in the Light of a Number of Variables - A Field Study in Schools of the First Cycle of Basic Education in Jablah City - عليان رنا; روعة عارف جناد (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The aim of this research is to determine the level of Positive Thinking among sixth-grade learners in schools in the city of Jableh, and to identify the differences in the level of Positive Thinking among sixth-grade learners in the light of variables such as gender, place of residence, attendance at kindergarten, and relocation after the February 6th earthquake. The researcher used a descriptive approach and developed a scale for Positive Thinking, which was applied to a sample of (269) male and female learners from the first cycle of basic education in Jableh. The research results showed that the level of Positive Thinking among sixth-grade students is average overall, and there is a superiority in Positive Expectations for the Future compared to other dimensions among the learners. There were no differences between males and females in overall Positive Thinking. There were no differences between learners who relocated after the February 6th earthquake and those who did not relocate in overall Positive Thinking, but there were differences in the dimensions of Positive Expectations for the Future and Positive Feelings, favoring learners who did not relocate from their homes. There were differences between learners who attended kindergarten and those who did not attend in terms of Positive Thinking, favoring learners who attended kindergarten. There were no differences between learners living in rural areas and those living in cities in overall Positive Thinking, but there were differences only in the dimension of Positive Expectations for the Future, favoring learners living in rural areas.